Chromofluorogenic naphthoquinolinedione-based probes for sensitive detection and removal of Hg2+ in aqueous solutions. (February 2022) - Kumar, Ashwani; Hur, Won; Seong, Gi Hun; Kumar, Subodh; Chae, Pil Seok
Abstract: Mercury ions are an industrial and environmental toxin that need to be monitored and regulated in aqueous samples. We prepared six probes (1 –6 ) using a naphthoquinolinedione ring as a fluorophore platform that contains different substituents on the quinolone ring. All probes showed abilities to selectively bind Hg 2+, but their sensitivity to the detection of this metal ion significantly varied depending on the substituent pattern. Among these probes, probe 5 with Br and CN substituents on the quinolone ring was most effective for the sensitive detection of Hg 2+ in aqueous solutions. This probe showed a naked-eye color change from yellow to purple upon binding to Hg 2+ . A ratio-metric method using UV–visible absorption data gave a limit of detection (LOD) of 20 nM, while the fluorescence-based result yielded an LOD of 0.047 pM. When bio-samples such as human urine and serum were used as media, the fluorescence-based LOD of this probe for Hg 2+ detection increased to 50 nM. Probe 5 was also effective at detecting methylmercury, an organic mercury species, dissolved in drainage water or urine. Based on the results of DLS, FE-SEM, and DFT calculations, the probe appeared to form large aggregates and undergo photo-induced electron transfer (PET) upon Hg 2+ binding, both of which are responsible for the probe fluorescence quenching. Probe 5 also showed the ability to sense Hg 2+ within three different types of human cells: Brain cells (U87MG), Hela cells and skin cancer cells (SK-MEL28). Furthermore, this probe holds significant potential for on-site applications since various solid supports such as silica gel, filter papers and TLC plates were effectively used for sensitive and selective Hg 2+ sensing, following probe coating/adsorption. Graphical abstract: Probe 5 showed the ability to effective detect Hg 2+ in a buffer as well as bio-fluids such as humane urine and serum. The fluorescence-based LOD of this probe was found to be 0.047 pM for Hg 2+ detection. Image 1 Highlights: Six naphthoquinolinedione-based probes (1 –6 ) were prepared in two or three steps. The fluorescence emission of probe 5 was effectively quenched upon Hg 2+ addition. Probe 5 gave an ultra-sensitive LOD of 0.047 pM for Hg 2+ detection. Probe 5 was capable of effectively sensing Hg 2+ in bio-samples or within live cells. Photo-induced electron transfer (PET) is mainly responsible for the fluorescence quenching.